1979
DOI: 10.1136/hrt.42.4.396
|View full text |Cite
|
Sign up to set email alerts
|

Angina in cold environment. Reactions to exercise.

Abstract: SUMMARY Seventeen male patients with angina pectoris, and a history of increased severity of angina in the cold, performed submaximal bicycle exercise tests in a normal (20°C) and a cold environment (-10°C, 2-2 m/s wind velocity) wearing standardised clothing. Observations were made during and after serial short-term exercise periods each starting at 50 W, with continuous load increase of 10 to 30 W per minute, separated by 30-minute rest intervals.In the group as a whole, maximal work load decreased by 7 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 12 publications
(18 reference statements)
1
20
2
Order By: Relevance
“…Early studies attributed cold-induced angina to sympathetic activation, resulting in increased peripheral vascular resistance and blood pressure, and leading to a greater cardiac workload (increased rate-pressure product) for any given exercise intensity (1,10). In the present study, we did not find any significant difference in heart rate or rate-pressure product at any time point between the exercise tests performed at +20°C and at -20°C.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Early studies attributed cold-induced angina to sympathetic activation, resulting in increased peripheral vascular resistance and blood pressure, and leading to a greater cardiac workload (increased rate-pressure product) for any given exercise intensity (1,10). In the present study, we did not find any significant difference in heart rate or rate-pressure product at any time point between the exercise tests performed at +20°C and at -20°C.…”
Section: Discussioncontrasting
confidence: 39%
“…Despite a lowering of the ischemic threshold, exposure to extreme cold was not associated with a decrease in total exercise time, nor was it associated with any deleterious effects on cardiovascular function including serious ventricular arrhythmias. Previous studies have generally reported a lowering of the ischemic threshold on exposure to cold solely in patients suffering from coldinduced angina, suggesting that individual susceptibilities to cold exist (3,(8)(9)(10)(11). Most of these studies, however, used temperatures ranging from +6°C to -10°C.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lassvik et al,2 in 17 patients whose angina was worsened by cold, found that maximal workload with bicycle exercise was reduced by 7% at -10°C compared with 200 C. Heart rate, systolic arterial pressure, and rate-pressure product were significantly higher in the cold at submaximal exercise but at the onset of angina and at peak workload did not differ from the results at normal temperature. Our finding of a lower rate-pressure product at the onset of ischemia in cold-sensitive patients was not observed by Lassvik et al 2 This discrepancy may be due to differences in patient characteristics or methodology; for example, Lassvik et al reported data at the onset of angina, not the onset of ST depression.…”
Section: Previous Studiescontrasting
confidence: 49%
“…An ecological study comparing CVD risk factors of Czech, German and Israeli middle-aged men (Bobak et al 1999) showed an unfavourable risk profile in Czech men that is related to high blood pressure and elevated levels of fibrinogen, triglycerides and D-dimer, a thromboembolic disease marker reflecting an activation of coagulation and predicting subsequent cardiovascular death (Morange et al 2006). Some underlying cardiovascular diseases (such as angina pectoris, I20) may lead to severe deterioration in health conditions after a sudden change of ambient temperature (from heated interior to very cold outdoor conditions) that may ultimately cause myo cardial ischemia, acute myocardial infarction and sudden death (Lassvik & Areskog 1979, Hong et al 2003. The large effects in middle-aged males compared to females may be related to larger prevalence of CVD in middle-aged males (cf.…”
Section: Possible Causes and Mechanisms Of Different Cold Spell Effecmentioning
confidence: 99%